What is the equation of the line tangent to # f(x)=(3x-1)(2x+4) # at # x=-1 #?

Answer 1

#y=-2x-10#

Find #f'(-1)# for the slope of the tangent line at the point #(-1,-8)#.
#f(x)=6x^2+10x-4#
Recall that #d/dx[x^n]=nx^(n-1)#.
#f'(x)=12x+10#
#f'(-1)=-2#

We can express the tangent line's equation in point-slope form as follows:

#y+8=-2(x+1)#

Forming the slope-intercept:

#y=-2x-10#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the equation of the line tangent to the function f(x)=(3x-1)(2x+4) at x=-1, we need to find the derivative of the function and evaluate it at x=-1.

First, let's find the derivative of f(x): f'(x) = (3x-1)(d/dx)(2x+4) + (2x+4)(d/dx)(3x-1) = (3x-1)(2) + (2x+4)(3) = 6x - 2 + 6x + 12 = 12x + 10

Next, let's evaluate the derivative at x=-1: f'(-1) = 12(-1) + 10 = -12 + 10 = -2

Now, we have the slope of the tangent line, which is -2. To find the equation of the line, we also need a point on the line. Since the line is tangent to the function at x=-1, we can use this point to find the y-intercept.

Using the point-slope form of a line, y - y1 = m(x - x1), where (x1, y1) is a point on the line and m is the slope, we can substitute the values: y - f(-1) = -2(x - (-1)) y - f(-1) = -2(x + 1) y - f(-1) = -2x - 2 y = -2x - 2 + f(-1)

Finally, we substitute f(-1) into the equation: y = -2x - 2 + f(-1) y = -2x - 2 + (3(-1)-1)(2(-1)+4) y = -2x - 2 + (-4)(2+4) y = -2x - 2 + (-4)(6) y = -2x - 2 - 24 y = -2x - 26

Therefore, the equation of the line tangent to f(x)=(3x-1)(2x+4) at x=-1 is y = -2x - 26.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7